2015
DOI: 10.1186/s12876-015-0233-2
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic inside stent placement is suitable as a bridging treatment for preoperative biliary tract cancer

Abstract: BackgroundEndoscopic biliary stenting (EBS) is one of the most important palliative treatments for biliary tract cancer. However, reflux cholangitis arising from bacterial adherence to the inner wall of the stent must be avoided. We evaluated the use of EBS above the sphincter of Oddi to determine whether reflux cholangitis could be prevented in preoperative cases.MethodsFifty-seven patients with primary biliary tract cancer were retrospectively recruited for the evaluation of stent placement either above (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 21 publications
1
47
0
Order By: Relevance
“…However, it was possible that undrained areas of cholangitis developed if we conducted drainage for additional lobes for the control of cholangitis during NAC. The time of emergency endoscopic retrograde cholangiopancreatography (ERCP) was indicated when a patient developed acute cholangitis or jaundice because of a drained/undrained hepatic lobe after stent placement 16 . The stent patency period was determined by the interval between stent placement and occlusion or the day of the surgery.…”
Section: Methodsmentioning
confidence: 99%
“…However, it was possible that undrained areas of cholangitis developed if we conducted drainage for additional lobes for the control of cholangitis during NAC. The time of emergency endoscopic retrograde cholangiopancreatography (ERCP) was indicated when a patient developed acute cholangitis or jaundice because of a drained/undrained hepatic lobe after stent placement 16 . The stent patency period was determined by the interval between stent placement and occlusion or the day of the surgery.…”
Section: Methodsmentioning
confidence: 99%
“…We performed intraductal placement in more than half of the M‐FCSEMS patients to abate difficulties during surgery and stent‐related perioperative AEs by minimizing duodenobiliary reflux, PEP, and unnecessary covering of the bile duct. Thus, Japanese randomized controlled trial proposed that suprapapillary stent for PBD might be useful than transpapillary placement due to lower incidence of cholangitis and longer duration of stent patency, even inside PS . We thought that intraductal placement of the M‐FCSEMS would prolong the time to stent occlusion by minimizing of duodenobiliary reflux, like an inside PS.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, Japanese randomized controlled trial proposed that suprapapillary stent for PBD might be useful than transpapillary placement due to lower incidence of cholangitis and longer duration of stent patency, even inside PS. 21 We thought that intraductal placement of the M-FCSEMS would prolong the time to stent occlusion by minimizing of duodenobiliary reflux, like an inside PS. Suprapapillary PS placement with some modifications of the PS design such as adding lasso may help to minimize the risk of duodenobiliary reflux and PEP, like the M-FCSEMS.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach to improve stent patency for MBO treatment is intraductal placement. 8,10,[21][22][23] In theory, positioning the distal end of the stent in the bile duct may reduce duodenobiliary reflux; however, placing the stent in this location may make it difficult to remove. Recent studies on modified plastic stents with a long string demonstrated a lower incidence of cholangitis with longer patency and easy removal using the string.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on modified plastic stents with a long string demonstrated a lower incidence of cholangitis with longer patency and easy removal using the string. 22,23 Although robust evidence demonstrating the efficacy of intraductal placement of a covered SEMS is lacking, a prospective study of intraductal placement of a saddle-shaped covered SEMS with a long lasso has recently been reported. 21 The study showed durable stent patency (mean, 297 days), and removal at reintervention was successful in 87.5% of cases; however, the sludge formation rate was relatively high.…”
Section: Discussionmentioning
confidence: 99%